2020
DOI: 10.1002/ecm.1412
|View full text |Cite
|
Sign up to set email alerts
|

Experience may outweigh cue similarity in maintaining a persistent host‐plant‐based evolutionary trap

Abstract: Rapid environmental change can decouple previously reliable cues from important resources, causing specialized recognition systems to result in maladaptive behaviors. For native herbivorous insects, such evolutionary traps are often imposed by attractive invasive plants that prove harmful to their offspring. Despite the costs of ovipositing on a poor-quality host, evolutionary traps are expected to persist when overlapping cue sets (cue similarity) link decreased preference for the novel, unsuitable plant with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 126 publications
0
29
0
Order By: Relevance
“…This stands in contrast to other examples where host preference was remarkably inert and virtually unaffected by the local variation in host availability (e.g. Wehling & Thompson, 1997; Bergstrom et al ., 2004; Chandra & Hodge, 2021), sometimes even at a considerable cost, as in the case of the persistent acceptance for the oviposition of the introduced plant Thlaspi arvense , which is lethal to the larvae, by the butterfly Pieris macdunnoughii (Chew, 1977; Steward & Boggs, 2020). Most likely such differences in tempo of host repertoire evolution are caused by differences in the genetic architecture of the traits involved, something that we are only beginning to unravel.…”
Section: Future Directionsmentioning
confidence: 99%
“…This stands in contrast to other examples where host preference was remarkably inert and virtually unaffected by the local variation in host availability (e.g. Wehling & Thompson, 1997; Bergstrom et al ., 2004; Chandra & Hodge, 2021), sometimes even at a considerable cost, as in the case of the persistent acceptance for the oviposition of the introduced plant Thlaspi arvense , which is lethal to the larvae, by the butterfly Pieris macdunnoughii (Chew, 1977; Steward & Boggs, 2020). Most likely such differences in tempo of host repertoire evolution are caused by differences in the genetic architecture of the traits involved, something that we are only beginning to unravel.…”
Section: Future Directionsmentioning
confidence: 99%
“…2013). However, while several studies claim to have revealed an evolutionary trap (Table ), relatively few provide evidence of preference for the lower‐fitness outcome over higher‐fitness alternatives (Keeler & Chew 2008; Rodewald et al 2011; Augustine & Kingsolver 2018; Steward & Boggs 2020; Sun et al . 2020), which is a prerequisite for an evolutionary trap (Robertson et al .…”
Section: Impacts Of Behavioural Changementioning
confidence: 99%
“…2019b). For example, constraints imposed by behavioural plasticity on the evolution of host preferences may explain why native Pieris macdunnoughii butterflies continue to oviposit on invasive Thlaspi arvense , even though no larvae laid on T. arvense survive to adulthood (Steward & Boggs 2020).…”
Section: Behavioural Changes In Native Animalsmentioning
confidence: 99%
“…Therefore, unless there is evidence that eggs laid at different times are independent events (e.g., 54), analyses should not assume independence. Modern analytical methods can tackle these difficulties (23,72).…”
Section: Why Did I Need My Own Preference-testing Technique?mentioning
confidence: 99%